Current use and perceived barriers of emergency point-of-care ultrasound by African health care practitioners - Hoving, Daniël Jacobus van; Alenyo, Annet Ngabirano; Komagum, Faith; Lamprecht, Hein (African Journal of Emergency Medicine, 2022)
The African Federation of Emergency Medicine (AFEM) recommends the use of emergency point-of-care ultrasound (ePOCUS) as a core skill for health care practitioners in Africa. The study explored the use of ePOCUS by health care practitioners among AFEM members who work across Africa.